Challenges and trends of Blockchain Interoperability and multi-blockchain architectures - Silva, Pedro M. R. G.; Silva, Matheus Lázaro Honório da; Velasco, Gislainy; Carvalho, Sergio T. (Anais da Escola Regional de Informática de Goiás (ERI-GO); 2025: Anais da XIII Escola Regional de Informática de Goiás, 2025)
The blockchain landscape in healthcare has undergone significant transformations, transitioning from large public networks to customizable and private blockchains, raising questions about how to integrate multiple blockchains into a unified system. This paper examines emerging trends and persistent challenges in blockchain interoperability within healthcare datasharing systems. We investigate solutions including Polkadot, Hyperledger Cacti, and Cosmos, revealing gaps: the absence of general protocols for heterogeneous blockchain communication, reliance on external trust rather than cryptographic consensus in multi-chain transactions, and inadequate identity verification mechanisms. We identify Self-Sovereign Identity (SSI) and Decentralized Identifiers (DIDs) as promising approaches for the identity challenge, and multi-blockchain consensus protocols as an unexplored solution where nodes from multiple chains collaboratively validate cross-chain transactions.